2015
DOI: 10.1075/ssol.5.2.05con
|View full text |Cite
|
Sign up to set email alerts
|

Processing punctuation and word changes in different editions of prose fiction

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk This is only a preprint version of the citable published paper. The actual published version may be somewhat different due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
(43 reference statements)
1
6
1
Order By: Relevance
“…However, neither the attribution of a change nor its nature appeared to significantly affect participants' ability to correctly report it. These findings run contrary to our most recent observations (Parente et al, 2019), while being more consistent with the original findings by Carrol et al (2015). It is possible that the mere act of providing readers with an ostensible origin for a variant may change their attitude towards the task itself; this, coupled with the back-to-back presentation of each pair of sentences, could have led to more engaged and attentive reading and to less discrimination between substantive and minor variants.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, neither the attribution of a change nor its nature appeared to significantly affect participants' ability to correctly report it. These findings run contrary to our most recent observations (Parente et al, 2019), while being more consistent with the original findings by Carrol et al (2015). It is possible that the mere act of providing readers with an ostensible origin for a variant may change their attitude towards the task itself; this, coupled with the back-to-back presentation of each pair of sentences, could have led to more engaged and attentive reading and to less discrimination between substantive and minor variants.…”
Section: Discussioncontrasting
confidence: 99%
“…In these two studies, readers encountered pairs of sentences that differed in some way between the two editions in terms of lexis and/or punctuation. Carrol et al (2015), in sentences that had one or two changes, showed an increase in reading times to the ROI containing the change relative to the rest of the sentence that remained unchanged. There was no evidence in the reading record to suggest that changes to punctuation were less noticeable than changes to lexical items.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations